ULUMUL HADIST (Sejarah Pertumbuhan Dan Perkembangan Hadist) - Nurmilasari; Muhammad Ali (AL-BAYAN INSTITUTE, 2025)
Hadith, as the second primary source of Islamic law, plays a central role in shaping the norms, ethics, and legal framework of the Muslim community. This study is motivated by the need to re-examine the historical development of hadith more comprehensively, particularly in understanding its transition from an oral tradition to a systematically structured scientific discipline. The purpose of this research is to systematically explain the process of codifying and classifying hadiths, while analyzing the ontological, epistemological, and axiological dimensions that underlie it. This study employs a qualitative-descriptive approach through library research, drawing on classical and contemporary literature. The findings reveal that the development of hadith is not merely narrative in nature but forms an independent discipline characterized by a rigorous system of transmission, validation, and classification. Ontologically, hadith has transformed from an oral legacy into a legitimate scientific entity; epistemologically, it has evolved through strict methodologies such as isnad and matn criticism; and axiologically, hadith remains relevant as a source of values, ethics, and law in responding to the challenges of modernity. In conclusion, this integrative study on the history and methodology of hadith not only enriches the field of hadith sciences ('ulūm al-ḥadīth) but also strengthens the understanding of hadith's authority and function in contemporary Islamic life.